Environmentally sustainable practices at UK airports - Budd, Thomas; Budd, Lucy; Ison, Stephen (ICE Publishing, 2015)
In response to growing concerns about rising energy bills, long-term energy security and the environmental impacts of greenhouse gas emissions, airport operators worldwide are increasingly implementing new sustainable practices to help reduce costs, increase efficiency and reduce their environmental impacts. These initiatives include the installation of on-site wind turbines, biomass plants, and ‘smart' heating and lighting systems as well as other ‘green' initiatives including rainwater harvesting initiatives, improved recycling facilities and financial incentives to encourage staff to travel to work by modes other than the private car. Drawing on specific examples, this paper examines the ways in which UK airports have responded to the challenge of reducing the environmental impacts of operations for which they are directly responsible by implementing green and sustainable energy and working practices. The paper concludes by discussing the importance of sustainable airport practices in light of future growth in key emerging aviation markets.